Improving the Performance of DVB-T2 in High-Speed Train Communication Systems - Isnawati, Anggun Fitrian; Pamungkas, Wahyu; Praja, Muhammad Panji Kusuma; Ni’amah, Khoirun; Mendicute, Mikel (Engineering, Technology & Applied Science Research, 2025)
The development of Digital Video Broadcasting-Terrestrial (DVB-T2) technology has spread worldwide and been implemented in various wireless communication channel environments, including High-Speed Train (HST) communication. The HST channel’s characteristics, including extremely high speeds of up to 300 km/h and the presence of numerous multipaths, significantly degrade the performance of DVB-T2. This paper proposes a method to address these challenges by employing Bose-Chaudhuri-Hocquenghem (BCH) and block code LDPC channel coding, along with Minimum Mean Squared Error (MMSE) channel estimation and equalization. The proposed approach integrates HST channel modeling with a DVB-T2 communication system that has been modified to mitigate the effects of Doppler and multipath fading. The BCH outer code is designed to address burst errors, while the LDPC inner code is engineered to handle random errors. The efficacy of the channel estimation and MMSE equalization methods in HST channels has been demonstrated, ensuring the preservation of the orthogonality of the Orthogonal Frequency Division Multiplexing (OFDM) subcarriers used and the mitigation of Inter-Carrier Interference (ICI). To this end, we have simulated the performance of this research on HST channels with various digital modulation types (16-QAM, 64-QAM, and 256-QAM) and also the effect of the number of multipath fading scatterers and the variation of train speed. The results of this research demonstrate a significant BER reduction at Signal-to-Noise Ratio (SNR) 15 dB, where the BER value reaches 10-3 when using 16-QAM. Among the various modulation options examined, 256-QAM emerged as the most effective, demonstrating a performance enhancement of up to 85% compared to the baseline scenario without the proposed mitigation. The research findings underscore the significance of train speed in Bit Error Rate (BER) performance, indicating that an increase in train speed leads to a deterioration in BER performance. Furthermore, the study highlights the impact of the number of scatterers on BER performance, demonstrating that an increase in scatterers results in a decline in BER performance. The findings of this research further reinforce the efficacy of DVB-T2 integrated with high-speed rail transportation applications, which have begun to show significant growth in numerous countries.